Short Communication: Molecular identification of White Sea Squirt Didemnum sp. (Tunicata, Ascidiacea) colonies growing over corals in Raja Ampat Islands, Indonesia - LUTHFI ANZANI; HAWIS H MADDUPPA; I WAYAN NURJAYA; P JOANA DIAS (Society for Indonesian Biodiversity, 2019)
Abstract. Anzani L, Madduppa HH, Nurjaya IW, Dias PJ. 2019. Short Communication: Molecular identification of White Sea Squirt Didemnum sp. (Tunicata, Ascidiacea) colonies growing over corals in Raja Ampat Islands, Indonesia. Biodiversitas 20: 636-642. Indonesia is at the center of the Coral Triangle, the region with the world’s highest marine biodiversity. The Raja Ampat archipelago in east Indonesia has one of the oldest networks of marine protected areas in the country and is a top priority area for marine conservation. The area is however under anthropogenic pressure from growing tourism, developments and exploration of natural resources. The most likely associated introduction of non-native species is however largely unexplored. Colonial ascidians or ‘sea squirts’ comprise a high number of species, many of them reported as introduced or invasive worldwide. In this study, we investigate the presence of white colonial ascidian colonies noticed to overgrow sections of the coral reefs in central Raja Ampat. We use DNA barcoding to address the colonies’ species identification and explore haplotype diversity to determine the species native or introduced status. We produced 22 DNA barcodes belonging to four potential cryptic Didemnum sp. species present in the Raja Ampat archipelago, Indonesia. Overall, the high number of haplotypes found in the area suggest these to most likely to be native species. The present work represents, as far as the authors are aware, the first time that such species were investigated in Raja Ampat. We hope with this work to create awareness for the topic of introduced and invasive species in the area and motivate further studies in Indonesia.